Light block cipher algorithm for electric power industry - Tao WANG (Dianxin kexue)
With the development of computer technology,cryptographic algorithms were applied more and more widely in the field of information security.However,it has been a very important problem that how to achieve high performance,high security encryption algorithm and more convenient application in the software and hardware environment.In future grid environment,study of the electric power industry special lightweight block cipher algorithm can get rid of the actual state that only using general algorithm,also makes the information and the safety of the power system more self controlled.According to the electric power industry central business security requirements,the lightweight block cipher algorithm of special power of better performance,higher safety and more convenient application were realized.